PENGARUH PEER ATTCHMENT DAN GAYA HIDUP HEDONISME TERHADAP PERILAKU KONSUMTIF (FASHION) PADA MAHASISWA PENGGUNA SHOPEE - Haque, Alya Dita Mazaya; Zulfan, Abiyyu Fadhil; Afifah, Siti; Fahmy, Zulfa; Zikrinawati, Khairani (Investama : Jurnal Ekonomi dan Bisnis, 2023)
As we know, clothing or fashion is a necessity for all people, one of which is for some students who have a high sensitivity to a trend and consider it something very important. The purpose of this research is intended to; 1) know that there is an influence between Peer attachment on consumptive behavior, 2) there is an influence between hedonism and consumptive behavior, 3) there is an influence between peer attachment and hedonism on consumptive behavior. This research is quantitative research with purposive sampling as a sample collection method. The subjects in this study were students using the Shopee application with an age range of 17-28 years. The data obtained is the result of distributing questionnaires to the subject, namely, there is a simultaneous significant effect between Peer Attachment and Hedonic lifestyle on consumptive behavior with a sig value. 0.000<0.05. However, the Peer Attachment variable partially does not have a significant effect on the consumptive variable with a sig value. 0.807> 0.05, and the hedonic variable has a sig value. 0.000 <0.05 which means that the hedonic variable has a significant effect on the consumptive variable partially.